Pengaruh Intensitas Bermedia Sosial, Efikasi Diri, dan Konformitas Terhadap Prokrastinasi Tugas Akhir dengan Regulasi Diri sebagai Variabel Intervening - NilaYunita Susanti; Ahmad Nurkhin (Journal of Accounting, Economics, and Business Education, 2025)
This study uses a type of quantitative research with a population of all Economics Education students at Semarang State University class of 2019 who are still active in June 2024, the sample used was a saturated sample of 119 respondents but only 115 respondents filled out the questionnaire. The data collection method used is the survey method by distributing questionnaires. The data analysis technique uses descriptive statistical analysis and Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using SmartPLS 4. Based on the results of the research hypothesis test, it shows that social media intensity, self-efficacy, and conformity have a negative and significant effect on self-regulation. Social media intensity and conformity have a positive and significant effect on final project procrastination. Meanwhile, self-efficacy has no effect on procrastination. Self-regulation can mediate the relationship between social media intensity and conformity on final project procrastination. Meanwhile, self-regulation cannot mediate the relationship between self-efficacy and final project procrastination. Self-regulation has a negative and significant effect on final project procrastination.